KRIMINALITAS JANUARI-JUNI 1928 DALAM KORAN BINTANG BORNEO - Michael Silvester Mitchel Vinco; Cahaydewi, Nadya (Amarthapura: Historical Studies Journal, 2022)
Crime is deviant behavior carried out by humans that is not in accordance with the basic norms of society. Actions that violate a rule in society in a social environment. One of the acts that violates societal norms is theft, theft, fraud and many more. This behavior can be subject to applicable penalties. The problem that will be discussed is how crimes occurred in 1928 and what crimes occurred in that year. The method used is descriptive qualitative, namely a type of research that utilizes qualitative data and is described descriptively. The results of this research aim to explain the crimes that occurred in 1928 within a period of 6 months.